Regulatory effects of IRF4 on immune cells in the tumor microenvironment - Lu, Jing; Liang, Taotao; Li, Ping; Yin, Qingsong (Frontiers in Immunology, 2023)
The tumor microenvironment (TME) is implicated in tumorigenesis, chemoresistance, immunotherapy failure and tumor recurrence. Multiple immunosuppressive cells and soluble secreted cytokines together drive and accelerate TME disorders, T cell immunodeficiency and tumor growth. Thus, it is essential to comprehensively understand the TME status, immune cells involved and key transcriptional factors, and extend this knowledge to therapies that target dysfunctional T cells in the TME. Interferon regulatory factor 4 (IRF4) is a unique IRF family member that is not regulated by interferons, instead, is mainly induced upon T-cell receptor signaling, Toll-like receptors and tumor necrosis factor receptors. IRF4 is largely restricted to immune cells and plays critical roles in the differentiation and function of effector cells and immunosuppressive cells, particularly during clonal expansion and the effector function of T cells. However, in a specific biological context, it is also involved in the transcriptional process of T cell exhaustion with its binding partners. Given the multiple effects of IRF4 on immune cells, especially T cells, manipulating IRF4 may be an important therapeutic target for reversing T cell exhaustion and TME disorders, thus promoting anti-tumor immunity. This study reviews the regulatory effects of IRF4 on various immune cells in the TME, and reveals its potential mechanisms, providing a novel direction for clinical immune intervention.